Elderly care in changing societies: Concurrences in divergent care regimes – a comparison of Germany, Sweden and Italy. (July 2018) - Theobald, Hildegard; Luppi, Matteo
European countries are facing social changes that are challenging their long-term care (LTC) systems in different ways. The ageing population and the decrease of care potential in families have led to different paths of modification to traditional care regime organization. This article compares the LTC policies of Sweden, Germany and Italy, three countries that have traditionally been regarded as representatives of distinct regime types in care regime typologies. The interrelation between policy reforms, changing state support, patterns of care arrangements and the commodification of care work is compared between the three countries. The analysis aims to reveal the basic dimensions of (changing) LTC policies and their effects in these countries; trends of convergence and divergence between the three regimes; and the main characteristics of the changed care regimes. Despite a trend to convergence characterized by a redefined involvement of and a complex mixture of state, market and family resulting in an increased precarization of care labour, the countries analysed still represent different care models. In particular, the amount of state support, the emphasis on family care versus professional services, and the role of different state levels in the governing system and reform paths are the key elements that mark the organization of national LTC.